Crash characteristics and injury risk of adult car occupants in near-side impacts. (4th July 2022) - Shaikh, Junaid; Lubbe, Nils; Sunnevang, Cecilia
Abstract: Objective: In the US, 27% of car occupant fatalities occur in side-impacts. Near-side impacts cause more serious injuries than far-side impacts. Car occupant safety overall has improved, but rear-seat occupant protection lags behind front-seat protection. The current study had two aims: first, to describe crash characteristics and injury outcomes for near-side rear-seated restrained occupants before and after side-impact regulations (FMVSS-214) were mandated; and secondly, to estimate injury risks in near-side impact depending on seating position, delta-v, and other predictors. Methods: The National Automotive Sampling System – Crashworthiness Data System (NASS – CDS) database for 1995 to 2015 was analyzed. The descriptive statistics focused on rear-seated restrained adults, comparing old (<1997) and new (≥1997) vehicles exposed to near-side impacts. Weighted logistic regression models including all front and rear-seat occupants were used to predict the occurrence of at least moderate injury in near-side impacts. Results: Rear-seated restrained adults in new vehicles were exposed to higher delta-v and intrusion levels compared to old vehicles. Moreover, injuries to rear-seat occupants in new vehicles were more distributed across body regions, compared to old vehicles (mainly thorax and head). The risk of sustaining injuries increased significantly with delta-v and occupant age, when not using a seatbelt, when seated in a passenger car and when hit in the passenger compartment. The risk increased by trend, but not significantly, when seated in a newer vehicle, when seated in the rear-seat and when the crash opponent was an SUV or van. Conclusions: Trends and risk factors for at least moderate injuries in near-side impacts were identified to guide future directions for occupant protection in side-impacts and its assessments.